2023
DOI: 10.1123/ijspp.2021-0464
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Determining the Alactic Time Span in Connection with Assessment of the Maximal Rate of Lactate Accumulation in Elite Track Cyclists

Abstract: Purpose: Following short-term all-out exercise, the maximal rate of glycolysis is frequently assessed on the basis of the maximal rate of lactate accumulation in the blood. Since the end of the interval without significant accumulation (talac) is 1 of 2 denominators in the calculation employed, accurate determination of this parameter is crucial. Although the very existence and definition of talac, as well as the validity of its determination as time-to-peak power (tPpeak), remain controversial, this parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…The finding that none of our participants attained the maximal calculated power output during the sprints is in line with our previous observations [ 28 , 30 ]. Due to the initial resistance during the acceleration phase of the sprints, when the athletes reached the point of producing the highest power, they were potentially fatigued.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding that none of our participants attained the maximal calculated power output during the sprints is in line with our previous observations [ 28 , 30 ]. Due to the initial resistance during the acceleration phase of the sprints, when the athletes reached the point of producing the highest power, they were potentially fatigued.…”
Section: Discussionsupporting
confidence: 93%
“…The motoric test was carried out 30 min after the 12-s sprint and involved each participant cycling for 6 s at the maximal rate and with low resistance [ 30 ]. This setting enabled a pedaling rate of ≥160 rpm to be attained within the first 3 s, thereby generating data at high pedaling rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method proposed by Mader [12], estimates lactic power by measuring the change in lactate concentration (ΔBLC) after a sprint test in relation to the test duration. This approach was for instance employed during a maximal isokinetic cycle sprint [13,14] and utilizes the determined maximal rate of lactate formation in the blood as a valid indicator of maximal glycolytic power [15]. It is proposed that higher rates of lactate formation correspond to higher glycolytic flux [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was subsequently supported by Hauser et al [24], who reported the highest rates after 6-second sprints when comparing sprint durations ranging from 6 to 20 seconds. Moreover, a study conducted with elite track cycling sprinters demonstrated a linear increase in ΔBLC from approximately 2.5 seconds to 12 seconds, indicating a potentially constant glycolytic flux during this time range [15]. The authors interpreted these linear segments as nearly linear parts of an exponential function, representing lactate accumulation during maximal efforts lasting up to 60 seconds or longer.…”
Section: Introductionmentioning
confidence: 99%